(untitled) (Hekima Review, 1992)
Bujo's last book (1) must be read as a challenge to any tendencies towards "clericalism", "episcopalism" or''sacerdotalism" that unfortunately are taking root in our dioceses, parishes and communities. The central question of the book concerns a Christian/African ethic. The question is: "Should (African) Christians rely morally on the "Magisterium" and/or a civil authority, or on something else? The question is not innocent. It stigmatizes the tendency in the Church to take for granted the idea that the Christian needs an authority, in the Catholic case the authority of an ecclesial Magisterium, for his or her ethnical decisions.